New synthetic phenylquinazoline derivatives induce apoptosis by targeting the pro-survival members of the BCL-2 family. (1st July 2022) - Eugin Simon, Samson; Ahmed, Usman; Saad, Syed Muhammad; Anwar, Ayaz; Khan, Khalid Mohammed; Tan, Ee Wern; Tan, Kuan Onn
Graphical abstract: Highlights: SMS-IV-20 and SMS-IV-40 potently induce apoptosis in MCF-7 and MCF-7-CR cells. The compounds chemo-sensitize MCF-7 and MCF-7-CR cells expressing MOAP-1, Bax, and RASSF1a. When combine with ABT-737, both compounds enhance apoptotic cell death in MCF-7-CR cells. The compounds down-regulate the expression of BCl-2, BCL-XL, or both in MCF-7-CR cells. Abstract: Chemo-resistant cancer cells acquire robust growth potential through cell signaling mechanisms such as the down-regulation of tumor suppressors and the up-regulation of pro-survival proteins, respectively. To overcome chemo-resistance of cancer, small molecule drugs that interact with the cell signaling proteins to enhance sensitization of cancer cells toward cancer therapies are likely to be effective for the treatment of chemo-drug resistant cancer. To identify high potency small molecules, a series of ten novel phenylquinazoline derivatives were synthesized to determine their cellular effects in MCF-7 and MCF-7- cisplatin-resistant (CR) human breast cancer cells which led to the identification of two bioactive compounds, SMS-IV-20 and SMS-IV-40, that exhibited an elevated level of cytotoxicity against the human breast cancer cells and spheroid cells. In addition, both compounds enhanced chemo-sensitization of the human breast cancer cells that were genetically engineered to express the tumor suppressor and pro-apoptotic proteins, MOAP-1, Bax, and RASSF1a (MBR), suggesting that the compounds interact with the MBR signaling pathway. Furthermore, when MCF-7-CR cells were treated with SMS-IV-20 and SMS-IV-40 in the presence of ABT-737, a BCL-XL and BCL-2 inhibitor, enhanced chemo-sensitization was observed, suggesting SMS-IV-20 and SMS-IV-40 exert antagonistic activity to regulate the functional activity of BCL-2 and BCL-XL. Western blot analysis showed that both SMS-IV-20 and SMS-IV-40 induced down-regulation of BCL-2 or both BCl-2 and BCL-XL expression, respectively while promoting the release of mitochondrial Cytochrome C . Taken together, the data showed that SMS-IV-20 and SMS-IV-40 are potent activators of apoptosis that enhance chemo-sensitization through their antagonistic actions on the pro-survival activity of the BCl-2 family in human cancer cells.